High level expression in Escherichia coli of soluble, enzymatically active schistosomal hypoxanthine/guanine phosphoribosyltransferase and trypanosomal ornithine decarboxylase. - Craig, S P (1991)
The bacterial alkaline phosphatase (phoA) promoter and signal peptide have been used previously to control recombinant expression and secretion of eukaryotic proteins in Escherichia coli. Other reports have shown that this expression system can generate relatively modest levels of active hypoxanthine/guanine phosphoribosyltransferase (HPRT; hypoxanthine phosphoribosyltransferase; IMP:pyrophosphate phosphoribosyltransferase, EC 2.4.2.8), which carries part of the signal peptide but remains in the cytosol of the bacteria. Herein, the phoA promoter without its associated signal peptide is used to regulate expression of the HPRT of Schistosoma mansoni and the ornithine decarboxylase (ODC; L-ornithine carboxy-lyase, EC 4.1.1.17) of Trypanosoma brucei, two enzymes that have been identified as potential targets for antiparasitic chemotherapy. The levels of recombinant expression range from 20% to 60% of the total bacterial protein, and the majority of both recombinant enzymes was soluble. The specific activity for the recombinant trypanosomal ODC was one-third to two-thirds that of the authentic native enzyme and yields were predicted to be 15-30 mg of active enzyme per liter of bacterial culture. The specific activity for the recombinant schistosomal HPRT was equivalent to that for the native enzyme purified from schistosomes and up to 10 mg of enzymatically active HPRT has been purified from a 0.5-liter culture of treated bacteria. These results represent a break-through in recombinant expression of HPRT and ODC.